The implementation of the rule of law as a necessary condition for the organization of law state - Пильгун, Н. В.; Рощук, М. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article describes the constitutional principal of the rule of law and its role in organization of lawstate. In this article elucidates the basic problems of the implementation of the rule of law.